Comparative performance of Barbari goats under different rearing system in semi-arid region - SINGH, M K; KUMAR, RAVINDRA; SINGH, S P (The Indian Journal of Animal Sciences, 2020)
This study was undertaken to compare the performance of Barbari goats under grazing system and stall feeding system. Thirty growing Barbari goats of average body weight 15.20±0.54 kg of about 6 months of age were divided into three equal groups (Gr 1, Gr 2 and Gr 3) of ten animals each as per completely randomized design. The animals of Gr 1 was fed with concentrate pellet having 16% Crude protein (CP) while Gr 2 animals were fed with concentrate pellet having 18% crude protein. Goats of Gr 3 were fed with a combination of Concentrate pellet (16% CP), Gram straw, greens along with 6 h grazing. Total body weight gain was highest in Gr 2 followed by Gr 1 and Gr 3. Duration of experimental feeding was 192 days. Average daily gain (g) was 75.28 in Gr 1, 82.77 in Gr 2 and 65.14 in Gr 3. Average daily gain was highest in Gr 2 fed with high CP concentrate pellet and statistically similar to Gr 1 but significantly higher than the Gr 3 kept on grazing with supplementation of concentrate pellet, gram straw and greens. The blood Hb, RBC, PCV, WBC, lymphocyte, monocyte and granulocyte were comparable (P>0.05) among the different groups. Upon DLC analysis, different leukocytes were in the normal range in the stall fed group compared to the grazing group. However, plasma cortisol and testosterone level was significantly (P < 0.05) higher in Gr 3 compared to Gr 1 and Gr 2. But the concentrations of plasma cortisol and testosterone were similar in Gr 1 and Gr 2. Present study concluded that the performance of Barbari goats was better under stall feeding system and farmers can gain more profit in stall feeding system of goat rearing compared to grazing system.